CSR Impact on Profitability: Insights from NSE Listed Firms - Kamalika Ray, Sachin Vilas Acharekar (European Economic Letters (EEL), 2024)
Corporate Social Responsibility (CSR) has long been identified as a significant topic of research. In the recent times, CSR has garnered significant interest in the business world due to its potential impact on a company's profitability. However, studies also show that the conclusiveness about this association between corporate social responsibility (CSR) and profitability remains equivocal. This study aims to provide a deeper understanding of this relationship between CSR and profitability in the context of India, evaluating selected industries of manufacturing, construction, transportation, energy, and agriculture. The study blends qualitative and quantitative analysis of secondary data of CSR expenditures and financial performance taken from 15 Indian National Stock Exchange (NSE) listed companies over a period of 2019-2023. The results reveals the positive and significant relationship between characteristics unique to a given sector and how they affect financial results. It demonstrates how businesses can create shared value by aligning CSR initiatives with societal welfare, ultimately leading to enhanced financial performance and sustainable growth. The paper would help in giving a perspective on how CSR impacts the different financial variables.